Serum adiponectin status among metabolic syndrome in Kuantan,Pahang - Md Aris, Mohd Aznan; Draman, Samsul; Abdullah, Nor Zamzila; Mohd Rus, Razman; Khattak, Muhammad Muzaffar Ali Khan (2011)
Background: Adiponectin is a collagen-like circulating protein secreted by adipocytes. Several studies have demonstrated that low adiponectin also has strong association with metabolic syndrome and its components such as obesity, insulin resistance, type 2 diabetes, dyslipidemia and coronary artery disease. Objective: To determine and compare the level of serum adiponectin between metabolic syndrome and non-metabolic syndrome subjects. Method: A cross-sectional comparative study was carried out among 76 participants of metabolic syndrome and 76 participants of non metabolic syndrome based on IDF criteria. This study was held at three primary care clinics and two villages in Kuantan, Pahang from 1st March to 30th September 2009. Results: The majority of respondents were Malay (88.8%) and female (57.9%) adult with mean age of 51 years old. Most of them are non-smoker (77.6%), hypertensive (51%) and diabetic (46.4%) with mean waist circumference of 88.5 cm and mean weight of 66.6kg. The metabolic syndrome group had a significantly lower adiponectin concentration than non-metabolic syndrome group (mean: 11.64 ug/ml vs 13.21 ug/ml; P<0.05). Conclusion: Hypoadiponectinemia was significantly associated with metabolic syndrome in Kuantan, Pahang.